2018
DOI: 10.7717/peerj.5564
|View full text |Cite
|
Sign up to set email alerts
|

Early Holocene morphological variation in hunter-gatherer hands and feet

Abstract: BackgroundThe Windover mortuary pond dates to the Early Archaic period (6,800–5,200 years ago) and constitutes one of the earliest archaeological sites with intact and well-preserved human remains in North America. Unlike many prehistoric egalitarian hunter-gatherers, the Windover people may not have practiced a sex-based division of labor; rather, they may have shared the load. We explore how mobility and subsistence, as reconstructed from archaeological data, influenced hand and foot bone morphology at Windo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
(185 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have also demonstrated differences in calcaneal morphology between populations having different lifestyles. Accordingly, hunter-gatherers or non-sedentary populations had taller and wider posterior calcaneus, wider anterior and middle talar facets, a protuberance on the dorsal aspect of the bone, and their internal structure included higher bone volume fraction than sedentary groups (Raichlen et al, 2011;Weiss, 2012;Hoover and Colette Berbesque, 2018;DeMars et al, 2021;Harper et al, 2022b;Harper, 2023). Furthermore, it has been suggested that additional factors affected calcaneal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated differences in calcaneal morphology between populations having different lifestyles. Accordingly, hunter-gatherers or non-sedentary populations had taller and wider posterior calcaneus, wider anterior and middle talar facets, a protuberance on the dorsal aspect of the bone, and their internal structure included higher bone volume fraction than sedentary groups (Raichlen et al, 2011;Weiss, 2012;Hoover and Colette Berbesque, 2018;DeMars et al, 2021;Harper et al, 2022b;Harper, 2023). Furthermore, it has been suggested that additional factors affected calcaneal morphology.…”
Section: Introductionmentioning
confidence: 99%